Modeling the Influence of Muallim on Children's Educational and Religious Development in Maktab Education Systems - Ahmet Alibašić; Nedim Begović (Center for Studies in Advanced Science, 2026)
This study examines the implementation of Islamic education and religious development in maktabs in Bosnia and Herzegovina as non-formal Islamic educational institutions, with a focus on the perspective of muallims. The research employs a qualitative approach through structured interviews with muallims who have experience teaching in maktabs, both domestically and within diaspora communities. The study focuses on the development of children's religious training areas, the application of Islamic educational principles, as well as the approaches and teaching methods used.. Research results indicate that religious education designed methodically and didactically can simultaneously develop various dimensions of children's education, especially the intellectual and moral aspects. Although teachers strive to apply the basic principles of Islamic education, some principles, such as individualization and the unity of education, still face implementation limitations. An educational approach that emphasizes reinforcement, positive encouragement, and value transformation has been proven to be dominant in supporting the internalization of Islamic values and the holistic development of children's personalities.